The effect of intravenous and inhalation anesthesia in general on the cognition of elderly patients undergoing non-cardiac surgery: a systematic review and meta-analysis - Huang, Leilei; Zhang, Yong (Frontiers in Medicine, 2023)
Background: Postoperative cognitive dysfunction (POCD) is a postoperative complication that often occurs in the elderly. This systematic review and meta-analysis aim to compare intravenous anesthetics (propofol) with inhalation anesthetics (sevoflurane) on the occurrence of POCD in the elderly who underwent non-cardiac surgery.The investigators searched for published articles from PubMed, Embase, Web of Science, Scopus, Cochrane, and Clinicalkey databases.Clinical studies comparing the incidence of POCD in elderly patients undergoing intravenous or inhalation anesthesia in general were selected.Primary outcomes included the occurrence of POCD at 1, 3, 7 days. The secondary outcomes are the patient's plasma S-100β protein levels (pg*ml-1) and delayed neurocognitive recovery incidence 5 to 7 days after surgery.Results: Fifteen studies including 3,817 patients were enrolled in the systematic review. Ten studies involving 1,829 patients were enrolled in the meta-analysis. The results demonstrate that there is no difference between intravenous and inhalation group in the incidence of POCD within 1 to 7 days (95% CI 0.73 to 1.26, P=0.77) and the occurrence of delayed neurocognitive recovery 5 to 7 days after surgery (95% CI -353.15 to -295.44, P=0.28). Plasma S-100β protein levels in the intravenous anesthesia group are lower than those in the inhalation group (95% CI 0.48 to 1.24, P<0.001) Conclusion: For elderly patients undergoing non-cardiac surgery, 3 inhalation anesthesia was comparable to intravenous anesthesia in terms of the occurrence of short-term POCD. Inhalation anesthesia may cause greater damage to the nervous system, with delayed recovery of cognitive function after 5 to 7 days showing no difference.